(untitled) (Journal of Mechanical Engineering, 2015)
The effect of cast, cold rolling and hot rolling prior to cold rolling reduction on the hardness, electrical conductivity and grain size of annealed Al-6Mg alloys was studied. It was found that the hot rolling prior to cold rolling attend the higher strength due to precipitation of b-phase during hot rolling which hinder the dislocation movement. At higher temperature of annealing electrical resistivity decreses due to particle coarcening but in case of cast alloy it increases due to precipitation of b-phase. It is seen from the microstructure that the cold worked structures are comprised of elongated grains. It is also observed that the cold rolled alloy attained almost fully re-crystallized state after annealing at 400oC for 60 minutes.